Regular arrays of microdisc electrodes: simulation quantifies the fraction of 'dead' electrodes. - Ordeig, O; Banks, C; Davies, T; Del Campo, J; Mas, R; Muñoz, F; Compton, R (2006)
Arrays of microdisc electrodes have found widespread use in electroanalysis. These are commonly produced lithographically and practical arrays may contain up to hundreds of individual disc electrodes (e.g. of gold, platinum, indium,...) to maximise sensitivity and minimise limits of detection. Typically, however, the lithographic fabrication process is imperfect resulting in a significant fraction (often tens of percent) of electrochemically inactive electrodes. We demonstrate that a 2-dimensional simulation based on the diffusion domain approximation in conjugation with simple experiments on the ferrocyanide redox couple in aqueous solutions can be used to rigorously 'count' the number of active electrodes in a non-destructive fashion. The agreement with an independent count in which active electrodes are identified via electro-plating with copper followed by ex situ microscopic examination is quantitatively excellent.